Advanced analysis of various effects of water on natural gas HCCI combustion, emissions and chemical procedure using artificial inert species. (15th March 2019) - Ahari, Mehrdad Farajzadeh; Neshat, Elaheh
Abstract: The aim of current study is to investigate the effects of water addition on natural gas HCCI combustion. For this purpose, a thermodynamic multi-zone model coupled to a semi-detailed chemical kinetics mechanism, containing 53 species and 325 reactions, is used. First, the validation of the multi-zone model is carried out for four different operating modes. Then, five different amounts of water are added to the fuel and its effect on natural gas combustion is investigated. The method of adding water to the in-cylinder charge is such that the total amount of mass inside the combustion chamber and the overall air-fuel ratio are constant. Also, Chemical, dilution and thermal effects of water are studied using artificial inert species method. The results indicate that addition of water retards the start of combustion and decreases peak values of in-cylinder pressure and heat release rate. Adding of water up to about 3% increases the engine thermal efficiency and decreases exhaust emissions. It is reveal that the thermal effect of adding water on start of combustion and emissions formation is more significant than its dilution and chemical effects. Water addition, similar to other additives, may help to control the combustion process of a HCCI engine. Highlights: Effect of water addition on natural gas HCCI combustion is investigated. Artificial inert species method is used to estimate different effects of water. Thermal effect of water is greater than its dilution and thermal effects. Dilution effect of water is more significant than its chemical effect. Low water contents increase thermal efficiency and reduce exhaust emissions.